Influence of length and conformation of saccharide head groups on the mechanics of glycolipid membranes: unraveled by off-specular neutron scattering - Yamamoto, Akihisa; Abuillan, Wasim; Burk, Alexandra Serena; Körner, Alexander; Ries, Annika; Werz, Daniel B.; Demé, Bruno; Tanaka, Motomu (The journal of chemical physics, 2015)
The mechanical properties of multilayer stacks of Gb3 glycolipid that play key roles in metabolic disorders (Fabry disease) were determined quantitatively by using specular and off-specular neutron scattering. Because of the geometry of membrane stacks deposited on planar substrates, the scattered intensity profile was analyzed in a 2D reciprocal space map as a function of in-plane and out-of-plane scattering vector components. The two principal mechanical parameters of the membranes, namely, bending rigidity and compression modulus, can be quantified by full calculation of scattering functions with the aid of an effective cut-off radius that takes the finite sample size into consideration. The bulkier “bent” Gb3 trisaccharide group makes the membrane mechanics distinctly different from cylindrical disaccharide (lactose) head groups and shorter “bent” disaccharide (gentiobiose) head groups. The mechanical characterization of membranes enriched with complex glycolipids has high importance in understanding the mechanisms of diseases such as sphingolipidoses caused by the accumulation of non-degenerated glycosphingolipids in lysosomes or inhibition of protein synthesis triggered by the specific binding of Shiga toxin to Gb3.